Education on the Prevention and Early Detection of Pulmonary Tuberculosis Through Anamnestic Screening - Bermawi, Bastiana; Kurniasari, Diyan Wahyu; Prihatini, Prihatini; Aqmal, Ghezali Tristan; Hidayatih, Nurul; Az-Zahra, Firlana Dania (UKInstitute, 2026)
Pulmonary Tuberculosis remains a major public health problem in Indonesia. The elderly are a vulnerable group due to decreased immunity and comorbidities, while stigma and low awareness often hinder early detection. This Community Service activity aimed to improve elderly understanding of Pulmonary Tuberculosis prevention and early detection through interactive education and anamnestic screening. The innovation of this program lies in the use of the N-Gain Score to evaluate the effectiveness of health education at the community level. The activity involved health education through interactive lectures, discussions, and educational media (PowerPoint and booklet), followed by anamnestic screening using a structured questionnaire. A total of 29 elderly participants from Wonocolo District were included as a high-risk group. Effectiveness was assessed using pre-tests and post-tests with 10 multiple-choice questions, analyzed using the N-Gain Score. Results showed an increase in the average knowledge score from 70.34 to 94.48 (gain of 24.14 points). Fourteen participants achieved a high N-Gain category, 13 were moderate, and none were low. No Pulmonary Tuberculosis symptoms were detected during screening. This program effectively improved health literacy and awareness among the elderly. Supporting community-based efforts toward Pulmonary Tuberculosis elimination.